Application Research of a New Type of Filter for Dynamic Voltage Restorer - HAO Xiao-hong; FANG Shan-xin; CHEN Wei (Gong-kuang zidonghua, 2010)
On basis of analysis of detection methods of voltage sag such as voltage peak detection method,Fourier transform method,wavelet transform method,d-q transformation method and pqr instantaneous power method,the paper proposed a detection algorithm of dynamic voltage restorer(DVR) based on instantaneous reactive power theory.For the problem of poor real-time of a traditional ButterWorth low pass filter,it designed a new type of filter which is consisted of a band-stop filter in series with a low pass filter.The simulation results in Matlab/Simulink showed that the new type of filter can reduce the detection time to one third of fundamental cycle without reducing precise,and improve the real time of voltage sag detection.